Toxic effects of combined exposure of tritiated water and genistein on the growth and development of zebrafish and its mechanism - Cui, Fengmei; Zhang, Qixuan; Wan, Jun; Sun, Liang; Chen, Na; Xue, Huiyuan; Wang, Tianzi; Luo, Fajian; Chen, Qiu; Tu, Yu (Frontiers in Environmental Science, 2022)
In this study, the aim is to explore the toxic effect of combined exposure of tritiated water and genistein on the early growth and development of zebrafish. Tritiated water with 3.7*102 Bq/ml exposure alone did not affect the development of zebrafish embryos. However, the survival rate, hatching rate and heart rate of zebrafish larvae decreased combined exposure with genistein, and the abnormality rate and apoptotic cells in the embryos and the level of oxidative stress increased. The results of RNA sequencing showed that the combined exposure of tritiated water and genistein affected the gene expression of zebrafish embryos. Differential genes were mainly enriched in many pathways. The results of qRT-PCR showed that cyp19a1b and apoptosis-related genes were elevated in the combined-exposed group. When cyp19a1b gene in zebrafish larvae was knocked out by CRISPR/Cas9 technology, their heart rate and deformity rate eased. Tritiated water has a toxic and sensitizing effect on genistein, and the combined exposure of both induces obvious abnormal growth and development of zebrafish. cyp19a1b gene plays an important role in the toxic effects of combined exposure.